Ecological landscape assessment in a silvicultural system in the Urdaibai Reserve (Basque Country, Spain) - Orrantia, Oreina; Ortega-Hidalgo, M. Mercedes; Loidi, Javier (Mediterranean Botany, 2019)
Forestry industry has transformed deciduous Cantabrian colline landscape from very diverse ecosystems into exotic monospecific Pinus spp. or Eucalyptus spp. tree plantations. Our aim was to determine the biological quality present at a forested and protected river basin based on vascular plant communities’ field examination and cartographic and aerial information analysis. We have transformed vegetation maps into biological quality maps, readily interpreted in terms of conservation state for land management. We have tested the index along an anthropized but protected area in the Atlantic Iberian Peninsula (Urdaibai Biosphere Reserve –and Natura 2000 site, Basque Country) individually assessing 158 vegetation fragments included in ten quadrats of 25 ha each. A comparison of land use distribution between exotic coniferous plantations and native forests showed a ratio 11:1, and Quercus robur native forests have been fragmented and reduced to small patches, mostly below one ha (73.7% of fragments). The ratio real to potential cover revealed occupation below 8% of potential territory, confined to altitudes and slopes over 200 m asl and 30% respectively. Mean biological value of the basin (38.4% of maximum) correlated to conifer plantation surface and native forest emerged as the only vegetation unit attaining index values above 50%. A quantitative approach to determine whether local lowland oak forest could be considered at favourable conservation status involved studying co-variation between index values and fragment size by means of asymptotic models that would provide a maximum expected biological value associated to a minimum required surface (72.9% for ≥2.5ha). We have obtained the highest index values (77.1%) for forest patches ≥5.0 ha, although fragments over that threshold accounted for barely 2.9% of the basin. Oak forests are far from showing a favourable conservation status, revealing that actual protection policies provide little shelter to native forest where silvicultural policies rule the landscape.